Reimagining industry growth : strategic partnership strategies in an era of uncertainty - Varroney, Daniel A. (Ascent Audio, 2022)
Tap into the potential of strategic partnerships with industry associations in this groundbreaking new book Reimagining Industry Growth offers listeners a blueprint to harnessing the power of leading industry associations as strategic partners. By utilizing those partnerships, business leaders will become able to leverage the collective strength of the supply chain to overcome challenges, address uncertainty, mitigate risks, and position their industries for growth. The book provides an overview of strategic partnerships, how they work, and how they can be applied to industry relationships with trade associations. It includes: illuminating and factual case studies outlining strategic partnerships in five different industry segments; roadmaps for executives to apply the lessons learned from industry; success stories on leveraging relationships with trade associations; and advice on how to move the needle for entire industries via effective strategic partnerships and achieve unprecedented growth. Ideal for executives, managers, business leaders of all kinds, business students and professors, and association executives, Reimagining Industry Growth is a must-listen for anyone who hopes to tap into the potential strength and value of effective strategic partnerships.